أثر الملاعب المصغرة على المتغيرات البدنية ( السرعة الهوائية القصوى - السرعة - القوة الإنفجارية) لدى لاعبي كرة القدم أقل من 17 سنة - علال, رامي (Institut d'Éducation Physique et Sportive - Mostaganem 2024/2025, 2025)
من خلال تحليل نتائج هذه الدراسة ومقارنتها بالدراسات السابقة، يتضح أن استخدام الألعاب المصغرة يمثّل اتجاهًا حديثًا وفعّالًا في مجال التدريب الرياضي، خاصة لدى الفئات العمرية الناشئة. تشير نتائج الدراسة إلى أن الألعاب المصغرة لا تقتصر على تطوير صفة بدنية واحدة كما هو الحال في بعض التمارين التقليدية، بل تعمل بشكل متكامل على تنمية عدة جوانب في آنٍ واحد، مثل القوة، والسرعة، والرشاقة، والتحمّل، والمرونة، إضافة إلى تحسين القدرات الحركية والتكتيكية. وتكمن القيمة المضافة لهذه الألعاب في قدرتها على خلق بيئة تدريبية ديناميكية ومحفّزة، تجمع بين المتعة والتحدي، وهو ما يتماشى مع الخصائص النمائية لفئة أقل من 17 سنة، التي تتّسم بقدرة عالية على التعلم الحركي، وميول فطرية نحو اللعب، فضلاً عن سرعة الاستجابة للمثيرات الخارجية. ومن هذا المنطلق، فإن اعتماد الألعاب المصغرة ضمن خطط التدريب لا يُعدّ خيارًا ترفيهيًا أو بديلًا ثانويًا، بل أصبح ضرورة تربوية وتدريبية تسهم في رفع كفاءة البرامج الإعدادية وتُسهم في تحقيق نتائج ملموسة على صعيد الأداء البدني والمهاري. كما تُظهر المقارنات مع الدراسات السابقة أن هذه المقاربة التدريبية تواكب أحدث التوجّهات في علوم الرياضة، حيث تؤكد الكثير من الأبحاث الحديثة على أهمية دمج الجوانب البدنية والنفسية والمعرفية ضمن نشاط واحد لتحقيق ما يُعرف بـ"التعلّم السياقي"، الذي يُعزّز من ثبات الأداء وتطوره. لذلك، فإن توظيف الألعاب المصغرة وفق منهجية علمية واضحة وبرمجة مدروسة تضمن التنويع، والتدرّج، والتكامل، يجعل منها أداة استراتيجية فعّالة في إعداد اللاعبين الناشئين، سواء على المستوى البدني أو الفني أو حتى الذهني. // // // // // By analyzing the results of this study and comparing them with previous research, it becomes clear that the use of small-sided games represents a modern and effective trend in sports training, especially for younger age groups. The findings indicate that small-sided games do not focus solely on developing a single physical attribute, as is the case with some traditional exercises. Rather, they work comprehensively to enhance multiple aspects simultaneously, such as strength, speed, agility, endurance, and flexibility, in addition to improving motor and tactical abilities. The added value of these games lies in their ability to create a dynamic and motivating training environment that combines fun with challenge. This aligns well with the developmental characteristics of the under-17 age group, which is characterized by a high capacity for motor learning, an innate inclination toward play, and a quick response to physical stimuli. From this perspective, integrating small-sided games into training plans is not merely an entertaining or secondary option, but rather an educational and training necessity that contributes to enhancing the effectiveness of preparation programs and achieving tangible results in both physical and technical performance. Furthermore, comparisons with previous studies show that this training approach is aligned with the latest trends in sports science. Many recent studies emphasize the importance of integrating physical, psychological, and cognitive aspects into a single activity to achieve what is known as "contextual learning," which enhances performance stability and development. Therefore, the strategic implementation of small-sided games through a clear scientific methodology and a well-structured program that ensures variety, progression, and integration makes them an effective tool for preparing young athletes — physically, technically, and mentally.
MES-2025-19
Keywords: الملاعب المصغرة- المتغيرات البدنية- السرعة الهوائية القصوى- القوة الانفجارية- لاعبي كرة القدم أقل من 17 سنة // // Small-sided games – Physical variables – Maximum aerobic speed – Explosive strength – Under-17 football players